2018
DOI: 10.1177/1940161218771893
|View full text |Cite
|
Sign up to set email alerts
|

Framing the Taxation-Democratization Link: An Automated Content Analysis of Cross-National Newspaper Data

Abstract: Taxpaying constitutes a major opportunity for citizens to relate to their governments. Although it is true that paying taxes is a responsibility, it also entitles citizens to claim control over government spending, which may facilitate a greater democratization of a country’s political regime. Consistent with this reasoning, a growing body of scholarship has documented a positive relationship between the size of tax revenues extracted by the state and the adherence of the country’s regime to democratic values.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Opperhuizen et al, 2019), automated content analysis of news articles (e.g. Kananovich, 2018), sentiment analysis of Facebook posts (e.g. Ji et al, 2019), ‘crowdcoding’ for analysis of political sentiment on Twitter (Guo et al, 2019), or a myriad of other techniques (see Boumans and Trilling, 2016), that digital methods are upon us is undeniable.…”
Section: Introductionmentioning
confidence: 99%
“…Opperhuizen et al, 2019), automated content analysis of news articles (e.g. Kananovich, 2018), sentiment analysis of Facebook posts (e.g. Ji et al, 2019), ‘crowdcoding’ for analysis of political sentiment on Twitter (Guo et al, 2019), or a myriad of other techniques (see Boumans and Trilling, 2016), that digital methods are upon us is undeniable.…”
Section: Introductionmentioning
confidence: 99%
“…With computational tools, as opposed to manual content analysis, researchers can uncover general patterns, sometimes in large volumes of textual data (De Grove et al, 2020;Lewis et al, 2013), and tackle questions that might have been difficult to address with manual content analysis (Trilling & Jonkman, 2018). The approaches employed in this article, (a) using document similarity algorithms to identify text reuse (Nicholls, 2019;Vogler et al, 2020) and (b) fitting STMs to identify themes in news texts (Barberá et al, 2020;Kananovich, 2018) have been shown to produce reliable data to answer similar questions in the past. These approaches are only applicable to written text, which is the focus of this article, and do not consider non-written content.…”
Section: Methodsmentioning
confidence: 99%
“…In the context of emerging work on tax and ‘identity’ (Björklund Larsen 2017 ; Carrillo, 2020; Kananovich, 2018; Kiel, 2019; Sheild Johansson 2018; Simpson, 2008; Stanley, 2016; Walsh, 2018), there has been some work on taxpayer groups generally (Lo, 1990; Martin, 2008; 2013; Willmott, 2017). More broadly, political sociologists have examined the rise of professionalized citizen mobilization firms (Lee et al., 2013; Walker, 2014) that rise and fall at the behest of powerful clientele.…”
Section: Taxpayer Groups In the Landscape Of Advocacymentioning
confidence: 99%